Prevention and early detection of acute kidney injury in intensive care unit: a systematic review - Jamaludin, Thandar Soe Sumaiyah; Nurumal, Mohd. Said; Che Hasan, Muhammad Kamil; Rizuan, Siti Hajar Shah; Mohamed Faizal, Nur Fadhlin Farhanah (IIUM Press, 2022)
Acute Kidney Injury (AKI) is often associated with Intensive Care Unit (ICU) admission and results in a higher mortality rate around the world. The AKI cases have been rising for the past decade alongside the mortality rate. Literature has shown that early detection helps in overcoming the problem. This systematic review aims to identify the identify the relevant literature and to summarize the prevention and early detection of AKI in the ICU setting to reduce the morbidity and mortality rate of patients. A total of 20 articles identified in this review. This systematic review also is in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Relevant studies were identified based on the inclusion criteria with language filters but were limited to articles published from the year 2010 to 2020. Two reviewers independently conducted the quality assessment, data extraction, and analysis on all included studies. The result indicates there are several biomarkers which are helpful in detecting AKI such as Neutrophil Gelatinase-Associated Lipocalin (NGAL), Interleukin-18 (IL-18), Tissue Inhibitor of Metalloproteinase 2 (TIMP-2), Insulin-Like Growth Factor Binding Protein 7 (IGFBP-7), Protein C (PC), and soluble thrombomodulin (sTM). This review also addressed nursing responsibilities for early detection and prevention of AKI. Thus, severe cases of AKI and mortality cases associated with AKI can be minimized with better predictive and proper management.